Spatio-Temporal Land Use Change Analysis at Dutse International Airport Using Google Earth Imagery - Sani, Inuwa Sani; Wibowo, Adi; Imam, Mahmoud Zubair (MO.RI Publishing, 2025)
This study discusses spatial-temporal land use change around Dutse International Airport, Nigeria, using high-resolution Google Earth imagery of 2012, 2018, and 2023. Change was triggered by the development of an airport in 2014 and has brought about phenomenal changes, including urbanization and agricultural and vegetated land cover loss. With supervised classification in ArcGIS, aided by geometric correction and accuracy measurements (confusion matrix, user and producer accuracy, kappa coefficient), quantitative estimation of land use change over time is ascertained in the study. Findings reveal the steep decline of agricultural land from 452.41 ha in 2012 to 116.01 ha in 2023, and loss in vegetation from 278.33 ha to 104.42 ha. In contrast, cover of settlement expanded from 97.21 ha to 346.42 ha and road infrastructure expanded from 172.54 ha to 296.54 ha. The result indicates natural and agricultural landscape pressure induced by infrastructure-based development. The research suggests land use planning through zoning policy, ecological buffer zones, and remote monitoring to harmonize development and conservation of peri-urban ecosystems.